Real-world Treatment Patterns in Patients with EGFR Mutation-positive NSCLC Receiving a First-Line, First- or Second-generation EGFR Tyrosine Kinase Inhibitor in South Korea and Taiwan - Jae Cheol Lee; Jen-Yu Hung; Young-Chul Kim; Gee-Chen Chang; Seung Soo Yoo; Sheng-Hsiung Yang; Keith L Davis; Saurabh P Nagar; Aliki Taylor; Sung Yong Lee; Jin-Yuan Shih (Asian Pacific Journal of Cancer Biology, 2021)
Introduction: The preferred first-line (1L) treatment for epidermal growth factor receptor (EGFR) mutation-positive (EGFRm) advanced/metastatic non-small lung cancer (NSCLC) are EGFR-tyrosine kinase inhibitors (TKIs). However, most patients treated with 1L first- or second-generation (1G/2G) EGFR-TKIs acquire resistance; the EGFR T790M mutation is observed in ~30–50% of patients. We report real-world NSCLC treatment and T790M testing patterns in South Korea and Taiwan. Methods: Retrospective medical record review of EGFRm advanced/metastatic NSCLC patients from routine practice. 1G/2G EGFR-TKI initiation 1 January 2015–31 December 2017 (follow-up end date: last available medical record or August 2019). Study measures: demographic/disease characteristics, 1L/2L treatment, T790M testing. Results: In South Korea, 70% (164/235) and in Taiwan 89% (89/100) experienced 1L disease progression (median [range] follow-up: 22 [2.3–50.7] months). Of those with disease progression, 68% (111/164) and 62% (55/89) had T790M testing in South Korea and Taiwan, respectively. In South Korea, 43% (48/111) were T790M-positive with 88% (n=42/48) receiving osimertinib (mostly 2L). In Taiwan, 18% (10/55) were T790M-positive; 100% received osimertinib. Overall, 73% (120/164) and 63% (63/100) in South Korea and Taiwan, respectively, received 2L therapy, predominantly pemetrexed-containing regimens. Among patients with disease progression, 9% (14/164) and 24% (21/89) died before receiving 2L therapy in South Korea and Taiwan, respectively. Conclusion: In both countries, <70% with 1L disease progression were tested for T790M at any point from NSCLC diagnosis, suggesting resistance mutation testing could be improved. Treatment/testing patterns may have changed in both countries since study initiation due to osimertinib reimbursement changes beginning December 2017.